Responses of Microhyla ornata to the Toxicity of Phoskill - Maniyar*, Sadaf Ishaque Inamdar, Rafeek Ahmed (Journal of Ecobiotechnology, 2011)
The lethality of phoskill on Microhyla ornata was determined by Static renewal bioassay method (Finney, 1971).The tadpoles of M. ornata were exposed to lethal concentrations of 24hrs, 48hrs, 72hrs and 96hrs for 1hr and 2hrs to record the oxygen consumption and behavioral responses respectively. The results obtained were dose dependent with slight variations. At the concentration of 24h LC50 the behavioral activities were found decreased within 15 minutes duration, during the 2hrs exposure period followed by increase in their resting period. Oxygen consumption also was recorded lowest compared to exposures in other concentrations.